A Note on Dirac Operators on the Quantum Punctured Disk - Klimek, S.; McBride, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We study quantum analogs of the Dirac type operator −2z∂/∂z on the punctured disk, subject to the Atiyah-Patodi-Singer boundary conditions. We construct a parametrix of the quantum operator and show that it is bounded outside of the zero mode.